2017
DOI: 10.1504/ijtm.2017.083610
|View full text |Cite
|
Sign up to set email alerts
|

Technological innovation and emerging economy multinationals: the product cycle model revisited

Abstract: This paper assesses the continuing validity of three distinct propositions associated with the early versions of the product cycle model of Vernon (1966Vernon ( , 1979 or its extension to Third World Multinationals by Wells (1983Wells ( , 1986. This is in light of recent developments in the role of rapidly evolving technological capabilities in the competitive emergence and evolution of MNCs from emerging economies (EMNCs). The first product cycle proposition states that these firms have limited scope for inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Process innovation refers to the firms' development of new products through new technology or new production systems (Manual, 2005). Previously, researchers at organizational level measured firm process innovation through the firm usage of new technologies and firm commitment to research and development (Tolentino, 2017). The official store environment is basically the design of a retail store that communicates brand value to customers, provides brand experience and efficiently guides customers through the space (Kumar and Kim, 2014;Mohan et al, 2013).…”
Section: Firm Innovation Activitiesmentioning
confidence: 99%
“…Process innovation refers to the firms' development of new products through new technology or new production systems (Manual, 2005). Previously, researchers at organizational level measured firm process innovation through the firm usage of new technologies and firm commitment to research and development (Tolentino, 2017). The official store environment is basically the design of a retail store that communicates brand value to customers, provides brand experience and efficiently guides customers through the space (Kumar and Kim, 2014;Mohan et al, 2013).…”
Section: Firm Innovation Activitiesmentioning
confidence: 99%
“…Previous research has examined process innovation in different environments. For example, Tolentino (2017) evaluated organizations’ process innovation based on their commitment and usage of new technology for research and development. Ganzer et al (2017) demonstrated that process innovation develops and improves the textile products manufactured and delivered in Brazil.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choi et al (1996) challenge the traditional product life cycle model view that products are sold sequentially across the world, and introduce the type of business system of a country and the role of emerging countries in global competition, in breaking this pattern. Tolentino (2017) challenges three main propositions associated with the product life cycle model, namely, the scope for innovation, which the author thinks that nowadays is broader for multinational corporations from emerging economies; the location of innovation, which the original theory always places at the home country of the product, can now be conducted also in a developed country and not only in the home country of the product, as their markets are also sophisticated; and finally the role of technological change and accumulation in allowing emerging economies to participate in the innovation process, taking into consideration not only demand, but also supply side factors.…”
Section: Literature Reviewmentioning
confidence: 99%